Customer Satisfaction of Technopreneurs Based on TQM and Servqual During the Covid-19 Pandemic - Sahala Siallagan (Asian Journal of Business and Accounting, 2023)
Manuscript type: Research paper Research aims: This research examines the influence of total quality management (TQM) on service quality (Servqual), TQM on customer satisfaction, and Servqual on customer satisfaction. Design/Methodology/Approach: A sample of 406 customers who made online purchase transactions from technopreneurs in the 33 districts of North Sumatra province was included. The participants were selected using multiple-stage cluster sampling. The sample size of 406 was determined through simple random sampling using the Krejcie and Morgan (1970) table at a 95% confidence level, resulting in a final sample of 198 customers. The collected data were analysed using Pearson correlation analysis. Research findings: TQM significantly influenced Servqual and customer satisfaction, while Servqual directly affected customer satisfaction. Theoretical contribution/Originality: This research provides valuable insights and contributions to technopreneurs by enhancing their managerial knowledge pertaining to customer satisfaction. Practitioner/Policy implication: This research proposes quality management as a strategic approach to enhance technopreneur development. Research limitation/Implications: For future research, there is potential to examine customer satisfaction among technopreneurs during the post-Covid-19 pandemic period.